Fool for Christ: The Political Thought of J.S. Woodsworth - Mills, Allen (University of Toronto Press, 1991)
James Shaver Woodsworth (1874-1942) stands as one of the half-dozen most important national political figures in twentieth-century Canadian history. Allen Mills acknowledges his outstanding achievements while providing a critical account of the Woodsworth legacy and revising the received opinion of him as a man of unbending conviction and ever-coherent principle. A product of western Canada's pioneer society and a stern Methodist household, Woodsworth grew up to make his way into social service and politcal action. A member of parliament for over twenty years, he rejected the traditional forms of political activity, seeking a new politics and a new political party. The latter turned out to be the Co-operative Commonwealth Federation founded in 1932. Its first leader was Woodsworth himself. In a crucial period between the World Wars, Woodsworth helped define the character of the modern Canadian, non-Marxist Left and of many of Canada's important economic and social institutions. Among them are the welfare state, the Bank of Canada, and Canada's internationalist role in the contemporary world.–Publisher's description.
Book available at Internet Archive to people with print disabilities: https://archive.org/details/foolforchristpol0000mill/mode/2up OCLC: 246743306